El COVID 19 y su impacto económico en el sector del transporte urbano en Riobamba periodo 2018 - 2023 - Gavin Ñauñay, Dennys Fabricio (2024)
ABSTRACT: This research seeks to determine the direct impact that the COVID 19 health crisis had on the economy of the transportation sector of the city of Riobamba. Initially, a descriptive statistical analysis was developed, to later develop a panel data model with information from the 7 companies that provide public transportation service in the city of Riobamba, taking income as a dependent variable and the number of passengers as independent., number of turns and transportation costs. The main results obtained reveal that the COVID-19 pandemic has had a significant and measurable impact on the urban transportation sector in Riobamba, with the number of users as the variable that most influences the decrease in income, without leaving aside from the expenses variable, which is also statistically significant. These results are directly attributable to mobility restrictions, the change in the population's behavior patterns, and the fear of contagion.